Genetics of aldosterone-producing adenomas with pathogenic KCNJ5 variants - Lerario, Antonio M. (Endocr Relat Cancer, 2019)
Somatic variants in genes that regulate intracellular ion homeostasis have been identified in aldosterone-producing adenomas (APA). Although the mechanisms leading to increased aldosterone production in APA cells has been well studied, the molecular events that cause cell proliferation and tumor formation are poorly understood. In the present study, we have performed whole exome sequencing (WES) to characterize the landscape of somatic alterations in a homogeneous series of APA with pathogenic KCNJ5 variants. In the WES analysis on eleven APA, 84 exonic somatic events were called by 3 different somatic callers. Besides the KCNJ5 gene, only two genes (MED13 and ZNF669) harbored somatic variants in more than one APA. Unlike adrenocortical carcinomas, no chromosomal instability was observed by the somatic copy-number alteration and loss of heterozygosity analyses. The estimated tumor purity ranged from 0.35 to 0.67, suggesting a significant proportion of normal cell infiltration. Based on the results of PureCN analysis, the KCNJ5 variants appear to be clonal. In conclusion, in addition to KCNJ5 somatic pathogenic variants, no significant somatic event that would obviously explain proliferation or tumor growth was observed in our homogeneous cohort of KCNJ5-mutated APA. The molecular mechanisms causing APA growth and tumorigenesis remain to be elucidated.